Hepatic artery pseudoaneurysm following percutaneous transhepatic cholangiogram: an extremely rare complication. Issue 7 (12th July 2019) - Tirumanisetty, Pratyusha; Sotelo, Jose William; Rander, Aditya; Syed, Taussif
Abstract : A 72-year-old female patient who was admitted for ischaemic stroke had developed ascending cholangitis. Percutaneous transhepatic cholangiogram was performed to drain the infected bile, but this was complicated by haemorrhagic shock and hepatic haematoma. Mesenteric angiogram showed right hepatic artery (RHA) pseudoaneurysm which was embolised, there by stopping her bleeding. RHA is normally located posterior to common bile duct (CBD). An uncommon location of RHA is anterior to CBD, which can lead to haemorrhagic complications during percutaneous cholangiogram.